Sistem Informasi Koperasi Berbasis Web Pada Koperasi Pegawai Negeri Dinas Pendapatan Daerah Provinsi Jambi - Gearidinda Anisa, Atlantita; Siahaan, Kondar (LPPM Universitas Dinamika Bangsa, 2023)
The Jambi Provincial Revenue Service Cooperative is a cooperative managed by Civil Servants at the Jambi Provincial Revenue Service. For now, cooperatives have not used information systems effectively, because cooperatives have not digitally processed data yet. The Design of a Web-Based Cooperative Information System for the Civil Servant Cooperative of the Jambi Provincial Revenue Service uses the PHP programming language and uses object-based modeling techniques to describe system analysis and design, namely in the form of use case diagrams, class diagrams, and activity diagrams. The output of this research is in the form of a prototype design system for Analysis and Design of a Web-Based Cooperative Information System at the Civil Servant Cooperative, Jambi Province Regional Revenue Service. For further research, it can be complemented with other data management.